Psychosocial Correlates of Emotional Eating Among Healthcare Professionals in a Tertiary Care Centre in Mysuru - Sayana Basheer; Praveen Kulkarni; R. Pragadesh; A Vanmathi (APIK Journal of Internal Medicine, 2025)
Introduction: People’s food preferences and eating habits are heavily influenced by their psychological health. Emotional eating (EE) is not a distinct eating disorder, but rather a subtype within a range of different eating behaviors that are affected by habits, stress, emotions, and personal eating attitudes. Stress and eating are frequently unhealthy companions for those in the medical field. This study proposes to determine the prevalence and psychosocial correlates with EE among health-care professionals. Materials and Methods: A cross-sectional study was done among 320 health-care professionals at JSS Hospital, Mysore, over 6 months using a convenient sampling technique. A pretested, semistructured self-administered questionnaire was used to collect information regarding sociodemographic characteristics, perceived stress (Perceived Stress Scale), EE (Emotional Eaters Questionnaire), and eating and lifestyle habits of participants. Statistical tests such as Chi-square tests and Spearman’s correlation test were used. Results: Among 320 health-care professionals, 82.8% were emotional eaters. Among emotional eaters, 28.8%, 42.5%, and 11.5% were low, emotional, and very emotional eaters, respectively. Among the study subjects, 77.19% had moderate stress and 13.12% had severe stress. There was a statistically significant association between age, perceived stress, and fried food intake with EE. Conclusion: The findings raise concerns over the high prevalence of EE among health-care professionals, calling for close attention from policymakers to address this new health challenge. Enhancing dietary habits, body weight status, exercise, and perceived stress levels could be potential targets for interventions.